IT TOOLS IN ENGLISH LANGUAGE LEARNING - Kadirova, Feruza Xikmatullaevna (INTERNATIONAL CONFERENCES, 2023)
In this article, we discuss the idea about how Information and Communication Technologies – particularly the internet- can be developed as a tool to support independent learning. From my point of view, both new media and education are closely connected. Moreover, the internet has several functions that might be explored for academic purposes.